2013
DOI: 10.1186/1471-2180-13-52
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of non-O1/non-O139 Vibrio choleraeisolated from hospitalised patients in China

Abstract: BackgroundCholera is still a significant public health issue in developing countries. The aetiological agent is Vibrio cholerae and only two serogroups, O1 and O139, are known to cause pandemic or epidemic cholera. In contrast, non-O1/non-O139 V. cholerae has only been reported to cause sporadic cholera-like illness and localised outbreaks. The aim of this study was to determine the genetic diversity of non-O1/non-O139 V. cholerae isolates from hospitalised diarrhoeal patients in Zhejiang Province, China.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 48 publications
(51 reference statements)
1
41
1
2
Order By: Relevance
“…Toxigenic non-O1/non-O139 V. cholerae strains appear to be frequently isolated from both clinical and environmental samples worldwide and are reported to be highly diverse (39,40). Variability among the isolates of this study was observed, with 55 profiles comprising up to 12 virulence factors (Table 5).…”
Section: Discussionmentioning
confidence: 82%
“…Toxigenic non-O1/non-O139 V. cholerae strains appear to be frequently isolated from both clinical and environmental samples worldwide and are reported to be highly diverse (39,40). Variability among the isolates of this study was observed, with 55 profiles comprising up to 12 virulence factors (Table 5).…”
Section: Discussionmentioning
confidence: 82%
“…While most of these putative virulence factors are expressed in only a fraction of clinical NOVC isolates, RTX, HapA and VCC are expressed in almost all V. cholerae serogroups and are therefore more promising as potential toxigenic factors [2], [9], [11]. VCC is a particularly interesting candidate; in a study using a streptomycin-fed murine model of disease, VCC was shown to be the predominant cause of death [12].…”
Section: Introductionmentioning
confidence: 99%
“…The isolates were selected based on their different gene characters (types of ctxB, rstR, and VSP-I/II), different years, and different provinces/regions; all 76 isolates represented the different characters of O139 isolates in China, from both clinical and environmental sources (see Table S2 in the supplemental material). Seven housekeeping genes (adk, gyrB, metE, mdh, pntA, purM, and pyrC) were targeted for MLST analysis, based on a previous study (22); primers are listed in Table S1 in the supplemental material. The PCR products were visualized on an agarose gel, and direct sequencing was performed in both directions.…”
Section: Bacterial Isolates and Serological Identificationmentioning
confidence: 99%